If (x-3) is a factor of x -kx -2 then the value of k is
Answers
Answered by
5
★ Given :
x - 3 is a factor of x² - Kx -2
★ To find :
The value of k
"★ Solution"
If x - 3 is factor of f(x) , then f(3) should be equal to 0 by factor theorem..
f(x) = x² - Kx - 2
f(3) = 3² - k(3) - 2
= 9 - 3k - 2
= 7 - 3k
7 - 3k = 0
7 = 3k
★ Additional Information :
Factor theorem : x – a is a factor of the polynomial p(x), if p(a) = 0. Also, if x – a is a factor of p(x), then p(a) = 0, where a is any real number.
Remainder theorem : Let p(x) be any polynomial of degree greater than or equal to one and let a be any real number. If p(x) is divided by the linear polynomial x – a, then the remainder is p(a).
Answered by
1
★Answer:
g(x)=x-3
p(x)=x²-kx-2
g(x)=0
now,
x-3=0
x=3
therefore,
x=3
substitute in p(x)
p(x)=x²-kx-2
p(3)=3²-3k-2
9-3k-2=0
7-3k=0
7=3k
k=7/3
Similar questions